Depletion of Uric Acid Due to SLC22A12 (URAT1) Loss-of-Function Mutation Causes Endothelial Dysfunction in Hypouricemia - Ichida, Kimiyoshi; Hisatome, Ichiro; Hamada, Toshihiro; Ninomiya, Haruaki; Kuwabara, Masanari; Niwa, Koichiro; Kato, Masahiko; Ogino, Kazuhide; Yamamoto, Kazuhiro; Higashi, Yukihito; Maharani, Nani; Sugihara, Shinobu (Circulation Journal, 2015)
Background:Uric acid (UA) serves as an antioxidant in vascular endothelial cells. UA transporter 1 (URAT1) encoded by SLC22A12 is expressed in the kidney and vessels and its loss of function causes hypouricemia. The purpose of this study was to examine whether there is any endothelial dysfunction in patients with hypouricemia.Methods and Results:Twenty-six patients with hypouricemia (<2.5 mg/dl) and 13 healthy control subjects were enrolled. Endothelial function was evaluated using flow-mediated dilation (FMD). mRNA of UA transporters expressed in cultured human umbilical endothelial cells (HUVEC) was detected on RT-PCR. There was a positive correlation between FMD and serum UA in the hypouricemia group. URAT1 loss-of-function mutations were found in the genome of 21 of 26 patients with hypouricemia, and not in the other 5. In the hypouricemia groups, serum UA in homozygous and compound heterozygous patients was significantly lower than in other groups, suggesting that severity of URAT1 dysfunction may influence the severity of hypouricemia. Thirteen of 16 hypouricemia subjects with homozygous and compound heterozygote mutations had SUA <0.8 mg/dl and their FMD was lower than in other groups. HUVEC do not express mRNA of URAT1, suggesting the null role of URAT1 in endothelial function.Conclusions:Depletion of UA due to SLC22A12/URAT1 loss-of-function mutations causes endothelial dysfunction in hypouricemia patients. (Circ J 2015; 79: 1125–1132)